(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The article stems from my PhD research on the child as a model in theatre pedagogy. It reveals tacit relations between the child and the clown in Jacques Copeau’s thinking and the way in which the child becomes a model for learning clown language in Jacques Lecoq’s and Philippe Gaulier’s pedagogies. The aim is to problematize commonplaces about the child-clown relationship from a dialogue with different disciplines (anthropology, psychoanalysis, psychology, performance studies), in search of an expanded understanding of notions such as innocence, authenticity, singularity and creativity in the clown’s training within the French theatrical tradition of Copeau-Lecoq-Gaulier.